ANALISA ATRIBUT SENSORI COKELAT SUSU KACANG METE DENGAN METODE FREE CHOICE PROFILING [Analysis Of Sensory Attributes Of Milk Chocolate Filling Cashews With Free Choice Profiling Method] - Muhammad Isa Dwijatmoko (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2023)
Chocolate is a processed food product consisting of cocoa mass, sugar, cocoa butter, and added other flavors, such as cashew. Free choice profiling is a sensory analysis method using consumers as analysts. A total of 31 consumer panelists tasted 3 types of milk chocolate with cashews using this method and assessed the intensity of the 5 attributes and types, such as sweetness, aftertaste (nutty), hardness, mouthfeel (smooth), and color. Data analysis used One Way ANOVA and continued with Duncan's test and Tukey's test to determine there were significant differences between treatments with a 95% confidence interval and continued with Principle Component Analysis. The results of the analysis show that 3 milk chocolate products with cashew show a strong correlation between color and hardness attributes. DC products have a strong correlation with sweetness, VHC products have a strong correlation with hardness in slightly hard and color in dark brown, and SQC products have a strong correlation with aftertaste (nutty). The mouthfeel (smooth) attribute does not correlate with chocolate products because it is the farthest between each chocolate product.Keywords: milk chocolate, sensory, PCACokelat merupakan produk pangan olahan yang terdiri dari kakao massa, gula, lemak kakao, dan ditambah citarasa lainnya, seperti kacang mete. Free choice profiling merupakan salah satu metode analisa sensori dengan menggunakan konsumen sebagai analis. Sebanyak 31 panelis konsumen mencicipi 3 jenis cokelat susu dengan kacang mete dengan metode tersebut dan menilai intensitas 5 atribut dan jenisnya yaitu, rasa manis (sweetness), aftertaste (nutty), kekerasan (hardness), mouthfeel (smooth), warna (colour). Analisa data menggunakan One Way ANOVA dan dilanjutkan dengan uji Duncan serta uji Tukey untuk mengetahui adanya beda nyata antar perlakukan dengan selang kepercayaan 95% dan dilanjutkan analisis dengan Principle Component Analysis. Hasil analisa menujukkan 3 produk cokelat susu dengan kacang mete menunjukkan korelasi yang kuat antara atribut sensori warna (colour) dengan kekerasan (hardness). Produk DC berkorelasi kuat dengan rasa manis (sweetness), produk VHC berkorelasi kuat dengan kekerasan (hardnees) di agak keras dan warna (colour) di coklat tua, dan produk SQC berkorelasi kuat dengan aftertaste (nutty). Atribut mouthfeel (smooth) tidak berkorelasi dengan produk cokelat karena berada paling jauh antar setiap produk cokelat.Kata kunci: cokelat susu, sensori, PCA